Health camps for truck drivers: a community-based approach to wellness - Jagnani, Sahil; Chowdhury, Ankit; Saikia, Snigdha (International Journal Of Community Medicine And Public Health, 2025)
Background: Globally, non-communicable diseases (NCDs) are a leading cause of morbidity and mortality. Occupational lifestyle, particularly in professions like truck driving, increases exposure to NCD risk factors. Early detection at the community level is vital for prevention and ensuring well-being. M/S Primary Healthtech Private Limited, in collaboration with the Indian Institute of Technology Guwahati, developed “Mobilab” a portable, battery-operated, IoT-enabled biochemistry analyzer. To support early screening, health camps targeting truck drivers key contributors to the national supply chain were conducted. Methods: Two health camps were organized in Binola (Camp-1) and Greater Noida (Camp-2), screening 382 and 234 participants respectively over 8 days each. Screening used the Mobilab device to assess various biochemical and physiological parameters for early detection of NCDs. Results: Parameters tested included cholesterol (CHOL), triglyceride (TGL), LDL, HDL, uric acid (UA), creatinine (CRE), glucose (GLU), hemoglobin (HB), total bilirubin (TBIL), total protein (TP), albumin (ALB), globulin (GLO), and albumin/globulin ratio (A/G). Camp-2 showed higher prevalence of kidney issues (41.1%) and anemia (39%) compared to Camp-1 (26.18% and 18%, respectively). Diabetes prevalence was low in both camps: 2.88% in Camp-1 and 2.16% in Camp-2. Conclusions: This community-based screening among truck drivers in Binola and Greater Noida highlights the effectiveness of early NCD detection using portable diagnostic tools. The study underscores the importance of regular health check-ups, especially for kidney-related complications, and the need for sustained preventive healthcare initiatives for high-risk occupational groups.